Written in my own heart's blood eaudiobook - Gabaldon, Diana (Outlander, 2014)
Hurtled back through time more than two hundred years to 1743 Scotland, Claire Randall finds herself caught in the midst of an unfamiliar world torn apart by violence, pestilence, and revolution and haunted by her growing feelings for a young soldier, James Fraser.